Energy Storage Flywheel Rotors—Mechanical Design - Miles Skinner; Pierre Mertiny (Encyclopedia, 2022)
Energy storage flywheel systems are mechanical devices that typically utilize an electrical machine (motor/generator unit) to convert electrical energy in mechanical energy and vice versa. Energy is stored in a fast-rotating mass known as the flywheel rotor. The rotor is subject to high centripetal forces requiring careful design, analysis, and fabrication to ensure the safe operation of the storage device.